Analisis Return On Equity Pada KPRI ”SEHATI” - Shalihin, Muhammad; Nurulrahmatiah, Nafisah (Universitas Muhammadiyah Palembang, 2020)
Purpose – The purpose of this study was to determine the amount of ROE on KPRI